2015
DOI: 10.1242/jeb.106146
|View full text |Cite
|
Sign up to set email alerts
|

Feeding in billfishes: inferring the role of the rostrum from a biomechanical standpoint

Abstract: Perhaps the most striking feature of billfishes is the extreme elongation of the premaxillary bones forming their rostra. Surprisingly, the exact role of this structure in feeding is still controversial. The goal of this study is to investigate the use of the rostrum from a functional, biomechanical and morphological standpoint to ultimately infer its possible role during feeding. Using beam theory, experimental and theoretical loading tests were performed on the rostra from two morphologically different billf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…The roughness has been interpreted as a micro turbulence generator suppressing flow separation and reducing drag (Videler, 1995). A recent study using computed tomography scans and biomechanical analysis confirmed the suitability of the sword as a tool to slash prey, but also revealed a weak, poorly mineralised area near the base of the rostrum just in front of the eyes (Habegger et al, 2015). The results of this study made us aware of the significance of anatomical features in the same area we found between 1996 and 2007.…”
Section: Introductionsupporting
confidence: 72%
“…The roughness has been interpreted as a micro turbulence generator suppressing flow separation and reducing drag (Videler, 1995). A recent study using computed tomography scans and biomechanical analysis confirmed the suitability of the sword as a tool to slash prey, but also revealed a weak, poorly mineralised area near the base of the rostrum just in front of the eyes (Habegger et al, 2015). The results of this study made us aware of the significance of anatomical features in the same area we found between 1996 and 2007.…”
Section: Introductionsupporting
confidence: 72%
“…D) (Atkins et al , ). It is unknown whether billfish rostra suffer high strains or stresses, but this is likely, given the massive accelerations and cantilever bending they apply to their bills in rapid, slashing pursuit of small fishes (Domenici et al , ; Habegger et al , ). To our knowledge, there have been no studies of damage and bone material failure modes in fish bone, so it is possible that this remodelling morphology is not purely damage‐driven (e.g.…”
Section: Second Concept: Remodelling Is Orchestrated By Osteocytesmentioning
confidence: 99%
“…This is difficult to ascertain. On one hand, several studies suggest that the swordfish' bill has important hydrodynamic and feeding-related functions (Habegger et al 2015, Videler et al 2016) thus bill breakage could be seriously disadvantageous for swordfish. On the other hand, at least in billfishes, there are several reports of apparently healthy individuals with damaged, malformed or even missing rostra (Frazier et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming an isometric relationship in the growth of the snout, total snout length (TSL) was calculated for each case in relation to the distance from the tip to the breaking point. To add further correction, we observed the arrangement of the paired nutrient canals at the breaking point, as shown in cross sections, to compare it with a swordfish analysed by Habegger et al (2015). The allometric regression between TSL and body length (BL), from post operculum to tail fork, was obtained following McGowan (1988).…”
Section: Methodsmentioning
confidence: 99%